2017
DOI: 10.1136/bmj.j2011
|View full text |Cite
|
Sign up to set email alerts
|

Self reported outcomes and adverse events after medical abortion through online telemedicine: population based study in the Republic of Ireland and Northern Ireland

Abstract: Objectives To assess self reported outcomes and adverse events after self sourced medical abortion through online telemedicine. Design Population based study. Setting Republic of Ireland and Northern Ireland, where abortion is unavailable through the formal healthcare system except in a few restricted circumstances. Population 1000 women who underwent self sourced medical abortion through Women on Web (WoW), an online telemedicine service, between 1 January 2010 and 31 December 2012. Main outcome measures Succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
125
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(130 citation statements)
references
References 25 publications
4
125
0
1
Order By: Relevance
“…And second, would they have found their ensuing abortion experience acceptable? Various models of self‐managed medication abortion have been shown to be safe, effective and acceptable to users in a variety of settings, including online telemedicine in Ireland, community‐based distribution at the Thailand‐Burma border, and a service providing preabortion care with instructions about misoprostol use and postabortion follow‐up in Peru . However, the role played by the accurate instructions, medical advice and emotional support that were part of all of these models is likely to be a factor in their positive outcomes, and such information and support may not be offered by pharmacy sites simply selling medications.…”
Section: Discussionmentioning
confidence: 99%
“…And second, would they have found their ensuing abortion experience acceptable? Various models of self‐managed medication abortion have been shown to be safe, effective and acceptable to users in a variety of settings, including online telemedicine in Ireland, community‐based distribution at the Thailand‐Burma border, and a service providing preabortion care with instructions about misoprostol use and postabortion follow‐up in Peru . However, the role played by the accurate instructions, medical advice and emotional support that were part of all of these models is likely to be a factor in their positive outcomes, and such information and support may not be offered by pharmacy sites simply selling medications.…”
Section: Discussionmentioning
confidence: 99%
“…For decades, people around the world have relied on WHO‐recommended medications to terminate unwanted pregnancies, increasingly in contexts where formal‐sector abortion care is restricted, expensive, and/or inaccessible . Studies have suggested that when individuals have accurate information about medication abortion protocols and about what to expect, access to quality medications, and access to follow‐up care if needed, they can safely and effectively manage their own abortions …”
Section: Introductionmentioning
confidence: 99%
“…3 The women lived in the Republic of Ireland or Northern Ireland, where abortion laws are among the most restrictive in the world. Almost 95% reported successfully ending their pregnancy, 0.7% required a blood transfusion, 2.6% required antibiotics, and overall 9.3% experienced symptoms potentially requiring medical attention.…”
mentioning
confidence: 99%
“…There were no deaths. 3 We already know that medical abortion with mifepristone is one of the safest options and that it is highly effective. 5 6 We also know that clinician assessment of patient eligibility through telemedicine is effective.…”
mentioning
confidence: 99%
See 1 more Smart Citation